The practical encyclopedia of magic : conjuring tricks, stunts & baffling illusions - Einhorn, Nicholas (Lorenz Books, 2022)
Learn from an expert magician, step by step tricks, including card magic, stage and optical illusions, stunts, puzzles, party and dinner table pranks.